Bone formation in subcutaneous pocket after bone flap preservation - Wang, Wen‐xue; Jiang, Nana; Wang, Jian‐wei; Kang, Xin; Fu, Guang‐hui; Liu, Yu‐liang (Clinical case reports, 2016)
Key Clinical Message Residual periosteum developed periosteal bone formation in the pocket 10 years after cranioplasty, lumpectomy was conducted on the left lower abdomen under local anesthesia. Pathological sections revealed abundant osteocytes and mature bone matrix, and confirmed the bone formation on the residual periosteum. Residual periosteum developed periosteal bone formation in the pocket 10 years after cranioplasty, lumpectomy was conducted on the left lower abdomen under local anesthesia. Pathological sections revealed abundant osteocytes and mature bone matrix, and confirmed the bone formation on the residual periosteum.